The Pastoral epistles in the Greek New Testament for the English reader - Wuest, Kenneth S. (Grand Rapids, MI Eerdmans, 1952)
Includes bibliographical references and index.
Donated by Mrs F. Hunter. Autographed by author.
Keywords: Bible. N.T. Pastoral epistles -- commentaries